HADIS UDHIYYAH : Studi Pemahaman Hadis Kurban Kolektif di Masyarakat Telaah pada Corporate Social Responsibility - Pradana, Rizky Dwi; Nasyomia, Novia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research explores the community's understanding of the hadith regarding collective sacrifice, particularly in the context of Corporate Social Responsibility (CSR). The study is motivated by the widespread practice of animal sacrifice in institutional settings, such as schools and companies, which often lacks uniform reference to the hadith. The main objective is to analyze how the hadith of collective sacrifice where one cow or camel can be shared by seven individuals is understood and applied by the local community, especially in relation to CSR contributions. This qualitative research uses a descriptive analytical approach. The study was conducted in Cicalengka Village, Pagedangan District, Tangerang Regency, Banten. Data were collected through observation, interviews, and literature review. The findings indicate that although the community is familiar with the hadith and its provisions, the application of these teachings in various collective sacrifice settings remains inconsistent. Sacrifices offered by companies through CSR programs are often perceived differently from those carried out independently by individuals or groups. Additionally, there is a noticeable gap between the textual understanding of the hadith and its practical implementation, particularly in corporate or institutional contexts. This study highlights the need for a unified perspective in interpreting and applying the hadith of collective sacrifice across all sectors.